Road Accidents in a Himalayan State of India: A Spatio-Temporal Analysis of Fatality and Severity in Himachal Pradesh - Sharma, D. D.; Kumari, Santosh (National Geographical Journal of India, 2022)
Present paper is an effort to analyze the fatality in road accidents and to understand the different factors responsible for accidents in Himachal Pradesh. The factors have been studied under four broad categories and occurrence of accidents at different time periods has been also described. The present analysis also reveals that in urban areas the majority accidents occurred during 6:00pm-10:00pm and in rural areas 10:00am-2:00pm. There are number of weather conditions which are responsible for vehicle accidents yet larger number of accidents occurred in fine conditions because there are more number of vehicles on the road during that time. Surprisingly more accidents occurred in the open areas as a result of negligence. It has been also noted that the cars and jeeps was the main segment of vehicle that was found more often involved the in road accidents.